2021
DOI: 10.3389/fcimb.2021.663756
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Oral Microbial Community in Periodontitis Based on Integrated Data

Abstract: ObjectiveMicroorganisms play a key role in the initiation and progression of periodontal disease. Research studies have focused on seeking specific microorganisms for diagnosing and monitoring the outcome of periodontitis treatment. Large samples may help to discover novel potential biomarkers and capture the common characteristics among different periodontitis patients. This study examines how to screen and merge high-quality periodontitis-related sequence datasets from several similar projects to analyze and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 49 publications
(69 reference statements)
7
40
1
Order By: Relevance
“…Many studies have investigated the abundance of certain phyla and genera that differentiate between periodontal health and disease. Although many discrepancies exist between studies, a shift in relative proportions of the four most abundant phyla, including Bacteroidetes, Actinobacteria, Proteobacteria and Firmicutes, and more specifically a decrease in the abundance of Proteobacteria and Actinobacteria and increased abundance of Bacteroidetes and Firmicutes in periodontitis, is unvarying amongst different investigators ( Griffen et al., 2012 ; Wang et al., 2013 ; Cai et al., 2021 ). On a genus level, Treponema is overrepresented in periodontal disease ( Abusleme et al., 2013 ; Cai et al., 2021 ), and conversely Rothia, Actinomyces , and Neisseria dominate communities of health ( Abusleme et al., 2013 ; Rosier et al., 2020 ; Cai et al., 2021 ).…”
Section: The Oral Microbiome: Heroes and Villainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have investigated the abundance of certain phyla and genera that differentiate between periodontal health and disease. Although many discrepancies exist between studies, a shift in relative proportions of the four most abundant phyla, including Bacteroidetes, Actinobacteria, Proteobacteria and Firmicutes, and more specifically a decrease in the abundance of Proteobacteria and Actinobacteria and increased abundance of Bacteroidetes and Firmicutes in periodontitis, is unvarying amongst different investigators ( Griffen et al., 2012 ; Wang et al., 2013 ; Cai et al., 2021 ). On a genus level, Treponema is overrepresented in periodontal disease ( Abusleme et al., 2013 ; Cai et al., 2021 ), and conversely Rothia, Actinomyces , and Neisseria dominate communities of health ( Abusleme et al., 2013 ; Rosier et al., 2020 ; Cai et al., 2021 ).…”
Section: The Oral Microbiome: Heroes and Villainsmentioning
confidence: 99%
“…Although many discrepancies exist between studies, a shift in relative proportions of the four most abundant phyla, including Bacteroidetes, Actinobacteria, Proteobacteria and Firmicutes, and more specifically a decrease in the abundance of Proteobacteria and Actinobacteria and increased abundance of Bacteroidetes and Firmicutes in periodontitis, is unvarying amongst different investigators ( Griffen et al., 2012 ; Wang et al., 2013 ; Cai et al., 2021 ). On a genus level, Treponema is overrepresented in periodontal disease ( Abusleme et al., 2013 ; Cai et al., 2021 ), and conversely Rothia, Actinomyces , and Neisseria dominate communities of health ( Abusleme et al., 2013 ; Rosier et al., 2020 ; Cai et al., 2021 ). As the understanding of the species involved in the etiology of periodontitis grows, the relationship between such pathogens, pathobionts, and oral symbionts among and across one another has revealed a complex network comprised of antagonistic and synergistic interactions among members of the oral microbiome.…”
Section: The Oral Microbiome: Heroes and Villainsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is obvious that the dysbiosis of the microbiota causes differences in metabolic pathways and functions. Elevated levels of bacterial motility proteins and flagellar assembly may imply an increased invasive capacity of pathogenic bacteria in periodontitis ( Cai et al., 2021 ). Studies have shown that bacterial phenolic acid metabolites, especially phenylacetate and volatile sulfur compounds were positively associated with periodontal exploration depth ( Liebsch et al., 2019 ; Abdullah et al., 2020 ).…”
Section: Oral Microbiota-related Diseasesmentioning
confidence: 99%
“…Moreover, the effects of the oral microbiome on oral and dental health are well characterized ( 21 , 22 ). Upon the dysbiosis of the oral community, pathogenic taxa like Porhyromonas , Prevotella , Veillonella , or Actinomyces my take over and cause critical illnesses ( 13 , 23 ).…”
Section: Introductionmentioning
confidence: 99%